Analisis Potensi Bahaya Pada Proses Produksi Barecore Menggunakan Metode HAZOP dan OHS Risk Assessment - Indah Pratiwi; Indah Prasetya Ningrum (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
The process of making a barecore still uses traditional and simple human labor and machining technology. In the production process, there are several sources of danger found, namely: machines used, work attitudes, work methods, raw materials, and the resulting sawdust disturbs environmental quality. This study aims to identify, assess the risk of hazards in the production process as well as corrective actions to control hazards using the Hazard and Operability (HAZOP) method. The research steps were hazard identification, risk assessment and corrective action. For hazard risk assessment, the OHS Risk Assessment method is used. The results of this study found that there are four sources of danger, namely the work environment, humans, materials, and machines. The results of the risk assessment calculation obtained three risk values, namely low risk with the number of findings of 13 potential hazards, medium risk with the number of findings of 78 potential hazards and high risk with the number of findings of two potential hazards. Risk control efforts to reduce potential hazards can be done by: using personal protective equipment, adding boxes as wooden material containers, making standard operating procedures, and providing first aid facilities.